A Binary Deletion Channel With a Fixed Number of Deletions. (7th October 2014) - GRAHAM, BENJAMIN
Abstract : Suppose a binary stringx = x 1 . . . xn is being broadcast repeatedly over a faulty communication channel. Each time, the channel delivers a fixed number m of the digits ( m < n ) with the lost digits chosen uniformly at random and the order of the surviving digits preserved. How large does m have to be to reconstruct the message?